EL ESTUDIO DE LAS ETAPAS DEL APRENDIZAJE LÉXICO BASADO EN EL CATE-CIC. EL ESTUDIO DE LAS ETAPAS DEL APRENDIZAJE LÉXICO BASADO EN EL CATE-CIC - Hui-Chuan Lu (Revista de Lingüística y Lenguas Aplicadas)
<span style="font-size: 7.5pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; color: black; mso-ansi-language: EN-GB; mso-fareast-language: ES; mso-bidi-language: AR-SA;" lang="EN-GB">Taking the base of the Corpus of Taiwanese Learners of Spanish, created by Lu, and applying as special analytical instruments, we've tried to study the lexical development of the students learning Spanish as second foreign language. We've focused on the comparison of the combination of words used in different levels of learning in which we proposed a continuum for the degree of learnablity form the easiest to the most difficult as follows VPrep- V/N-Prep-N, V-Conj, V-Adv/V-N, N-Adj, V-Adj, Adj-N, N-V, Det-N. Moreover, we not only derived, in the developmental stages of learning, an order from early stage to late stage exists that comes from the orthographic type to the grammatical and then to lexical types; but we also identified that the semantic meaning appears in a stage later than the vocabulary with regard to the lexical type of the combinative words <div style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; background-image: initial; background-attachment: initial; background-origin: initial; background-clip: initial; background-color: #ffffff; margin: 8px;"> <span style="font-size: 7.5pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; color: black; mso-ansi-language: EN-GB; mso-fareast-language: ES; mso-bidi-language: AR-SA;" lang="EN-GB">Taking the base of the Corpus of Taiwanese Learners of Spanish, created by Lu, and applying as special analytical instruments, we've tried to study the lexical development of the students learning Spanish as second foreign language. We've focused on the comparison of the combination of words used in different levels of learning in which we proposed a continuum for the degree of learnablity form the easiest to the most difficult as follows VPrep- V/N-Prep-N, V-Conj, V-Adv/V-N, N-Adj, V-Adj, Adj-N, N-V, Det-N. Moreover, we not only derived, in the developmental stages of learning, an order from early stage to late stage exists that comes from the orthographic type to the grammatical and then to lexical types; but we also identified that the semantic meaning appears in a stage later than the vocabulary with regard to the lexical type of the combinative words